PERANAN GURU BK ( BIMBINGAN KONSELING ) DALAM PEMBENTUKAN KARAKTER SISWA DI SMP Negeri 9 Baubau - AMALUDDIN (Jurnal Pendidikan Sejarah, 2023)
The formulation of the problem in this research is what is the role of guidance and counseling teachers in forming student character at SMP Negeri 9 Central Baubau and what is the shape of student character at SMP Negeri 9 baubau. The aim of this research is to find out the forms of student character at SMP Negeri 9 Baubau and to find out the services of guidance and counseling teachers in forming student character at SMP Negeri 9 baubau. his research is this research using qualitative descriptive research. This is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The approach is directed at Bk teachers, school students and the school as a whole. Time and place: This research was conducted in 2020/2021 at SMP Negeri 9 baubau, the research subjects, namely: the head of SMP Negeri 9 baubau, the guidance counselor at SMP Negeri 9 baubau and the students of SMP Negeri 9 baubau. The instruments for this research were, Observation, interviews and document study. Based on the research that has been carried out, the results obtained are that the guidance and counseling teacher is a person who is fully responsible for implementing guidance and counseling at school in shaping the character of his students. The services used to shape student character are orientation and information services. The role of the guidance and counseling teacher has been proven to be able to shape the character of his students, but it has not been maximized, causing only some students to have the character of religious, honest, responsible, tolerant, diligent, disciplined, friendly, peace-loving where the guidance and counseling teacher gives a letter to the students' parents. three times, if the student's parents do not respond to the letter, the guidance and counseling teacher makes a direct visit to the student's parent's house as a form of the guidance and counseling teacher's role.